Land Theology: Intrigue View of Land According to the Culture of the Toba Batak People in Ecological Preservation - Siregar, Johnson P. Robinsar; Sihombing, Teddi Paul; Hutabarat, Ro Sininta (Eduvest - Journal of Universal Studies, 2023)
The study aims to provide a critical understanding of the views of Toba Batak culture to examine the issue of ecological damage. The study discusses a qualitative approach with literature studies. The results show land theology provides an explanation of the understanding of the value of land intrigue according to the Culture of the Toba Batak People that their ancestors valued the land so much that the land was his own identity. The value of land restriction understood by the ancestors of the Toba Batak people departs from the totalitarian understanding that microcosmic and macrocosmic connections explain how humans relate to God, humans to their environment and humans to humans. The relationship is arranged in a value system that makes the land so identical to itself that the ancestors of the Toba Batak people call that the land is surnamed. From this relationship then born philosophy as an ideal that became the purpose of the life of the Toba Batak community in its development so that the value and meaning of the land became lost. The Toba Batak community then as understood anthropomism made land as an instrument for achieving economic value. Land is no longer viewed from its intrinsic value in the cultural value of the Toba Batak people, causing ecological crises and conflicts. Therefore, if the Toba Batak community was born from a culture inherited from ancestors to the present. Thus loving Culture becomes concrete evidence of loving the land.